Accounting Cooperative System of Business Vocational High School in Jakarta - Sri Zulaihati; Santi Susanti (Budapest International Research and Critics University, 2018)
This research seeks to help the business continuity of the school cooperative, to solve the problem of cooperative sustainability as a learning center for students to improve the quality of education and relevance to the business world, access, efficiency and relevance of education to make higher competence of students in the senior high school level. Researchers see that school cooperatives have not been well managed because management resources do not maximize their potential, and the sustainability and development of school cooperatives tend to be stagnant, whereas the opportunity in order to maximize the cooperative's economic potential to improve the welfare of students is very wide open. School cooperatives also serve as laboratories for students to implement a dual system education is not optimal in its implementation, the involvement of students only to maintain the store, not to the stage of implementation of good management. This paper will explain how school cooperatives management in business vocational high school in Jakarta with qualitative research method